Adsorption behavior of modified porous starch to methyl blue in aqueous solution. Issue 3 (February 2020) - Zhao, Zhipeng; Jiang, Mengmeng; Mei, Chentao; Huang, Hui
Abstract: Porous starch was prepared by replacing ice crystals in frozen starch gel with ethanol using a solvent exchange method. It was then modified by phosphoric acid and urea via solid-state reaction to produce modified porous starch. The modified starch was used to adsorb methyl blue in aqueous solution. Five adsorption kinetics and five adsorption isotherm were used to fit the experimental data, and the fitting effect was evaluated using seven error analysis methods to get the best model.